Effect of Business Risk and Profitability on Capital Structure with Likuiditas As Moderation - Dwi Orbaningsih (International Ecsis Association, 2022)
The purpose of this study is to determine the effect of business risk and profitability on the capital structure with liquidity as a moderation variable. Quantitative methods were used in the study. The sample collection used purposive sampling of 11 companies listed on the IDX during 2017-2020. The analysis used moderation regression and classical assumption testing. The results showed that business risk and profitability affect the capital structure. Meanwhile, moderation variables are able to moderate the influence of business risk on the capital structure and are unable to moderate the effect of profitability on the capital structure.